1996
DOI: 10.1073/pnas.93.7.3126
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acute in vivo human immunodeficiency virus infection by human interleukin 10 treatment of SCID mice implanted with human fetal thymus and liver.

Abstract: To improve the usefulness of in vivo models for the investigation of the pathophysiology of human immunodeficiency virus (HIV) infection, we modified the construction of SCID mice implanted with human fetal thymus and liver (thy/liv-SCID-hu mice) so that the peripheral blood of the mice contained significant numbers of human monocytes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 24 publications
0
23
0
1
Order By: Relevance
“…First, it suggests that HIV employs Tat to enhance interactions between monocytic cells and T cells during HIV-1 infection. Since Tat is indispensable for HIV replication (28,40), and IL-10 is known to inhibit HIV replication in monocytic cells (23,24), Tat-induced IL-10 may prevent excessive HIV replication as a negative feedback regulator in monocytic cells. Since IL-10 is also known to prevent apoptosis in human monocytic cells (77), Tat may be a factor to prevent apoptosis of monocytic cells and thus promote the development of monocytic cells as viral reservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it suggests that HIV employs Tat to enhance interactions between monocytic cells and T cells during HIV-1 infection. Since Tat is indispensable for HIV replication (28,40), and IL-10 is known to inhibit HIV replication in monocytic cells (23,24), Tat-induced IL-10 may prevent excessive HIV replication as a negative feedback regulator in monocytic cells. Since IL-10 is also known to prevent apoptosis in human monocytic cells (77), Tat may be a factor to prevent apoptosis of monocytic cells and thus promote the development of monocytic cells as viral reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…We and others (13,17,18) have demonstrated that IL-10 is produced constitutively throughout the course of HIV infection, and following antiretroviral treatment, IL-10 levels are significantly decreased. We and others have also demonstrated that HIV infection of monocytic cells in vitro results in enhanced IL-10 production (17, 19 -21) which may be of significance because of the ability of IL-10 to induce immune unresponsiveness (22), to inhibit HIV replication (23,24), and to limit viral entry as a result of its inhibitory effects on the expression of chemokine receptors on T cells (25). However, because monocytes act as viral reservoirs during HIV infection (11,26), and because IL-10 has been shown to enhance CXCR4 expression on dendritic cells (27), increased IL-10 production may, in fact aid the virus to escape from host immune surveillance.…”
mentioning
confidence: 99%
“…57 Given the crucial role of immune activation in HIV disease progression, 58 it is possible that despite its inhibitory effect on T cells, IL-10 has a net beneficial impact during later stages of HIV infection by limiting systemic immune hyperactivation and CD4 T-cell loss. Third, the direct effects of IL-10 on virus production are complicated, as IL-10 has been reported to inhibit HIV replication in monocytes, 52,59 but also to induce expression of CCR5 in CD4 T cells, 60 which may hasten infection. A placebocontrolled trial investigating the tolerance and impact of recombinant IL-10 therapy on parameters of disease progression in HIV-infected individuals did not show significant changes in either viral load or CD4 T-cell counts during 4 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…47 More importantly, an in vivo study showed the inhibitory effect of IL10 on acute HIV infection. 48 In the light of our observations and the previously published reports implicating these genes in progression to AIDS, 18,19 further studies in other cohorts to clarify the possible pathogenic role of IL10 and IL4 variants (IL4_H2 and IL10_H10) are now seen to be imperative. The data that we have catalogued on polymorphisms, LD and haplotype patterns in the Th1-Th2 cytokine genes studied here can serve for these investigations in AIDS, and also in other immune-related disorders.…”
Section: Snp Genotyping Of Th1-th2 Cytokines In Aids Cohortmentioning
confidence: 85%